Annals of Industrial Engineering 2012 Industrial Engineering: overcoming the crisis - Prado-Prado, J. Carlos; García-Arca, Jesús; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2014)
The aim of CIO is to establish a forum for the open and free exchange of ideas, opinions and academic experiences about research, technology transfer or successful business experiences in the field of Industrial Engineering. The CIO 2012 is an annual meeting promoted by “Asociación para el Desarrollo de la Ingeniería de Organización” (Industrial Engineers Association, ADINGOR) with a  Scientific Committee composed of 61 international referees and more than 200 professionals from 7 countries. A selection of the lectures and presentations made over three days by researchers and practitioners from  different countries are presented here. A range of topics is covered including: ·         Business Administration & Economic Environment ·         Technological & Organizational Innovation ·         Logistics & Supply Chain Management ·         Production & Operations Management ·         Management Systems & Sustainability   The Conference in Industrial Engineering (CIO) and its proceedings are an excellent platform for the dissemination of the outputs of the scientific projects developed in the frame of the International Research and Development plans.
PART I.Business Administration & Economic Environment -- PART II.Technological & Organizational Innovation -- PART III.Logistics & Supply Chain Management -- PART IV.Production & Operations Management -- PART V.Management Systems & Sustainability -- PART VI.Papers prize-award.
Keywords: Industrial engineering; Production engineering; Industrial and Production Engineering